Population of Patients With Traumatic Brain Injury in Skilled Nursing Facilities: A Decade of Change. Issue 1 (January 2019) - Lueckel, Stephanie N.; Teno, Joan M.; Stephen, Andrew H.; Benoit, Eric; Kheirbek, Tareq; Adams, Charles A.; Cioffi, William G.; Thomas, Kali S.
Abstract : Objective: To describe the natural history of patients with traumatic brain injury (TBI) admitted to skilled nursing facilities (SNFs) following hospitalizations. Setting: Between 2005 and 2014. Participants: Adults who had incident admissions to skilled nursing facilities (SNFs) with a diagnosis of TBI. Design: Retrospective review of the Minimum Data Set. Main Measures: Main variables were cognitive and physical function, length of stay, presence of feeding tube, terminal condition, and dementia. Results: Incident admissions to SNFs increased annually from 17 247 patients to 20 787 from 2005 to 2014. The percentage of patients with activities of daily living score 23 or more decreased from 25% to 14% ( P < .05). The overall percentage of patients with severe cognitive impairment decreased from 18% to 10% ( P < .05). More patients had a diagnosis of dementia in 2014 compared with previous years ( P < .05), and the presence of a terminal condition increased from 1% to 1.5% over the 10-year period ( P < .05). The percentage of patients who stayed fewer than 30 days was noted to increase steadily over the 10 years, starting with 48% in 2005 and ending with 53% in 2013 ( P < .05). Conclusion: Understanding past trends in TBI admissions to SNFs is necessary to guide appropriate discharge and predict future demand, as well as inform SNF policy and practice necessary to care for this subgroup of patients.